TEEN PREGNANCY - Urbina, Claudia (2015)
OBJECTIVE: To determine the perinatal characteristics of pregnant adolescent women. DESIGN: Retrospective, descriptive study. SETTING: Edgardo Rebagliati Martins National Hospital, EsSalud, a teaching hospital. MATERIALS AND METHODS: We analyzed all deliveries attended in adolescents from January 2000 through December 2004. RESULTS: There were 443 deliveries in adolescents, average age 18,3 years, 16,3% of them (72) 17 year-old or less, and 83,7% (471) between 18 and 19 years. It was the first pregnancy in 81,3%, preterm delivery occurred in 17,1%, cesarean-section rate was 41,5%; 84,4% of the newborns weighed between 2500 and 3999 g and 12% less than 2500 g. CONCLUSIONS: Preterm delivery and perinatal mortality were higher in adolescents than in the hospital general pregnant population, mainly in the 17 year-old or less adolescent, becoming the higher risk group. Vaginal delivery was more frequent in the adolescent, but the incidence of cesarean- section increased in the adolescent 17 year-old or less in comparison with the 18 and 19 year-old.